Sosialisasi Mengenai Keselamatan dan Kesehatan Kerja pada Bidang Listrik di SMK Nurul Islam - Hardiyanti, Mega Rahayu; Priyana, Efta Dahrtikasari (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aimed to strengthen students’ understanding of Occupational Safety and Health (OSH), particularly for Electrical Engineering students at SMK Nurul Islam. During practical sessions, students often face risks such as electrical leakage, electric shock, and fire hazards. The activity included theoretical counseling on basic OSH concepts, guidance on electrical and fire safety, and mentoring discussions focused on identifying and preventing electrical hazards. This approach provided students with active, practical learning experiences that supported the direct application of knowledge in laboratory and workshop environments. The program also emphasized the importance of recognizing potential hazards before performing any task to minimize the likelihood of accidents. The results showed increased student competence in understanding electrical risks, applying preventive measures, and responding to fire emergencies. Overall, this activity is expected to serve as a preventive effort to reduce work-related accidents among vocational students during electrical practice in their daily practical activities.